Impoliteness Strategies Used in the Movie "Easy A" - Jojor Romanna Simanjuntak; Ambalegin Ambalegin (Humanitatis : Journal of Language and Literature, 2022)
The purpose of this study is to analyze the impoliteness strategies employed in Easy A. This research is proposed by Culpeper’s (2011) theory. In this study, the researchers analyzed impoliteness strategies using descriptive qualitative analysis. The subject of the research is “Easy A” movie. In this study, data was gathered by using an observational methodology and a non-participatory technique. After processing the data, pragmatic identification methods were used to analyze it. During this study, the researchers identified 16 utterances. The researchers discovered five kinds of impoliteness as a result of their research, including (4) bald on record impoliteness, (5) positive impoliteness, (4) negative impoliteness, (2) mock politeness, and (1) withhold politeness. Positive impoliteness and negative impoliteness were most frequently used by Easy A.